One Size Does Not Fit All: Sociodemographic Factors Affecting Weight Loss in Adolescents. (25th February 2020) - Cummins, Claire B.; Bowen-Jallow, Kanika; Tasnim, Sadia; Prochaska, John; Jupiter, Daniel; Wright, Alex; Hughes, Byron D.; Nunez-Lopez, Omar; Lyons, Elizabeth; Glaser, Andrea; Radhakrishnan, Ravi S.; Thompson, Debbe; et al.
Abstract : Successful lifestyle changes for weight reduction are heavily dependent on recognizing the importance of societal and cultural factors. Patients 13–19 years of age with a BMI ≥95 th percentile are eligible for our multidisciplinary adolescent weight loss clinic. A behavioral questionnaire was administered at the initial visit. Patients were seen every 4–6 weeks. Bivariate analysis was used to identify sociodemographic factors associated with differences in weight loss. Overall, receiving reduced cost meals was associated with a lower likelihood of losing weight (kg) (p < 0.01 ). When stratified by race, White adolescents were more likely to lose weight if caretakers reported having enough money to buy healthy food (p < 0.05 ); in contrast, Black adolescents were less likely to lose weight (p < 0.05 ). However, Black patients were more likely to lose weight if they reported eating fruits and vegetables (p < 0.05 ). Female adolescents were more likely to lose weight if they felt unhappy about their appearance (p < 0.05 ). Interestingly, male adolescents were less likely to lose weight if they felt unhappy about their appearance (p < 0.05 ). Social and cultural norms influence weight loss in adolescents in unique and differing ways. Culturally competent individualized interventions could increase weight loss in diverse groups of adolescents with obesity.